Designing a chair : sitting pretty - Auliffe, Mark; Bear, Damien; Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2002)
This program looks at chair design from two slightly different perspectives. The program looks at all aspects of the design process from the brief through to the evaluation of the final product by the client
Camera, Keiran Doolan ; writer, associate producer Simon Garner
Voice over : Peter Kent
For middle secondary to senior secondary students
Keywords: Chair design; Chairs; Design; Furniture design